PERLINDUNGAN HUKUM INFORMASI DATA PRIBADI DALAM KEGIATAN PINJAMAN ONLINE BAGI MASYARAKAT - Panjaitan, Sanjay Cluivert Adrianus; L Elly AM Pandiangan; Tomson Situmeang (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
Peer to Peer Lending is a loan agreement that is wholly or partly born with the help and facilities on a computer network that is connected to each other and the agreement is set forth in electronic documents and other electronic media. The implementation of peer to peer lending that are not in accordance with the provisions will cause losses to the community, especially because of the presence of personal data information. This study uses a normative juridical writing methodology, namely research conducted by examining library materials or secondary data. In this case based on laws, books, research results, doctrines, newspapers related to topics related to this writing. The protection of personal data information in peer to peer lending activities is very important given by the government because personal data information is a personal right that is guaranteed to be confidential. Existing regulations regarding the protection of personal data information in peer to peer lending still have limitations in law enforcement. Therefore, binding legal rules and strict sanctions are needed that can provide a deterrent effect for the perpetrators. In this case, it is necessary to form a special institution that handles legal protection so that the protection and management of personal data information in Indonesia can run well. With good legal protection, personal data information will provide a sense of security and comfort for people who carry out economic activities in Indonesia.